2022
DOI: 10.3390/s22093307
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Fire Detection and Notification System Based on Improved YOLOv4 for the Blind and Visually Impaired

Abstract: The growing aging population suffers from high levels of vision and cognitive impairment, often resulting in a loss of independence. Such individuals must perform crucial everyday tasks such as cooking and heating with systems and devices designed for visually unimpaired individuals, which do not take into account the needs of persons with visual and cognitive impairment. Thus, the visually impaired persons using them run risks related to smoke and fire. In this paper, we propose a vision-based fire detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…These are objective matrices that are helpful for a fair comparison of recognition techniques. In our previous studies [ 51 , 52 , 53 , 54 , 55 , 56 ], we computed metrics such as the F-measure ( FM ), precision, and recall. The FM is the weighted average that balances the measurements between the precision and recall rates.…”
Section: Resultsmentioning
confidence: 99%
“…These are objective matrices that are helpful for a fair comparison of recognition techniques. In our previous studies [ 51 , 52 , 53 , 54 , 55 , 56 ], we computed metrics such as the F-measure ( FM ), precision, and recall. The FM is the weighted average that balances the measurements between the precision and recall rates.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we rotated each original fire image and then flipped each rotated image horizontally to increase the number of images in the fire-detection dataset, as explained in detail in the refs. [ 9 , 11 , 12 ]. By applying the data augmentation methods to the original 7395 fire images, we increased the total number of images to 90,700.…”
Section: Proposed Fire-detection and Notification Methodsmentioning
confidence: 99%
“…Further research has shown that camera-based fire-detection systems achieve much better results with high prediction accuracy, low cost, and reduced processing time to enhance fire safety [ 7 , 8 , 9 , 10 ]. AI-based fire detection is a potentially powerful approach to detect flames and to warn building occupants in different indoor environments because it is highly distinctive, does not depend on colors, size, or shape, and is robust to illumination changes [ 11 , 12 ]. However, traditional computer vision or image processing approaches have been applied to simple fires and are appropriate only under certain conditions [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, spatial-level transformations affect both the notion and bounding box, making the transformation significantly more difficult to implement than pixel-level transformations. However, spatial-level changes have proven to be more successful in increasing the performance of object recognition and detection approaches [ 37 ]. Both setups were used in this study.…”
Section: Data Collection and Processingmentioning
confidence: 99%